2017
DOI: 10.18632/oncotarget.23710
|View full text |Cite
|
Sign up to set email alerts
|

Construction of key signal regulatory network in metastatic colorectal cancer

Abstract: There are many stages in the development and metastasis of colorectal cancer (CRC). In this study, we compared the differential expression genes in different stages of metastatic CRC. Then, we screened the continuously up-regulated genes and the continuously down-regulated genes that were associated with the development and metastasis of CRC. After analyzing the intersection of differential expression genes in each stage, we screened the continuously up-regulated genes and deviated genes in the extracellular m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 31 publications
2
7
0
Order By: Relevance
“…Mitogen-activated protein kinase 3 (MAPK3) belongs to the protein kinase superfamily and catalyzes the concomitant phosphorylation of a threonine and a tyrosine residue in the MAP kinase p38. It has been confirmed to be a potential therapeutic target for different kinds of human cancers, including CRC [43][44][45][46][47]. A previous study revealed that phosphorylated AMP-activated protein kinase (AMPK) expression in CRC was associated with superior prognosis among p-MAPK3 positive cases, indicating a possible interaction between the AMPK and MAPK pathways influencing tumor behavior [46].…”
Section: Discussionmentioning
confidence: 99%
“…Mitogen-activated protein kinase 3 (MAPK3) belongs to the protein kinase superfamily and catalyzes the concomitant phosphorylation of a threonine and a tyrosine residue in the MAP kinase p38. It has been confirmed to be a potential therapeutic target for different kinds of human cancers, including CRC [43][44][45][46][47]. A previous study revealed that phosphorylated AMP-activated protein kinase (AMPK) expression in CRC was associated with superior prognosis among p-MAPK3 positive cases, indicating a possible interaction between the AMPK and MAPK pathways influencing tumor behavior [46].…”
Section: Discussionmentioning
confidence: 99%
“…There are data indicating that miR-124 might contribute to the glucocorticoid resistance by promoting the proliferation and inhibiting the apoptosis (Vonlanthen et al 2014;Kim et al 2015;Huang et al 2016;Liang et al 2017). Furthermore, it has also been shown that NR3C1 is a key component of the regulatory pathway for signal transmission in mitochondria and that glucocorticoids can stimulate directly the mitochondrial transcription by the mitochondrially localized glucocorticoid receptors (Minchenko and Germanyuk 1984;Minchenko 1988;Minchenko and Tronjko 1988;Psarra and Sekeris 2011;Qi and Ding, 2017). Moreover, glucocorticoid receptors can also be a signal by binding to other transcription factors and modulate the transcriptional regulation of target genes (Khan et al 2011;Li et al 2012;Dasgupta et al 2015).…”
mentioning
confidence: 99%
“…Other researchers have also indicated an important role of the complex between VEGF-A and CCL7-CCR3 axis as a key node in the extracellular matrix of CRC cells in early metastatic stages. They have demonstrated that chemotaxis of inflammatory cells during this period (from stage II to III TNM) decreases in extracellular matrix and it might be connected with the established connection between CCL7-CCR3 and metalloproteinases (MMPs)/chemotactic factor family [86].…”
Section: Receptor For Eotaxinsmentioning
confidence: 96%